Diseño e implementación de una red multiservicios para el centro de atención ambulatorio “Batán” del Instituto Ecuatoriano de Seguridad Social - Ortega Ochoa, Cristian Javier (2017)
This project titled "DESIGNING AND IMPLEMENTATION OF A MULTISERVICIAL NETWORK FOR THE BATÁN OUTDOOR ATTENTION CENTER OF THE SOCIAL SECURITY ECUADORIAN INSTITUTE", details relevant factors to implement a network that supports the inclusion of new services such as video conferences, IP telephony, and service quality and so on. In order to offer to users a convergent communication network which lets them to interact with new and sophisticated technologies that facilitate the development of their daily duties and optimize resources. In chapter 1, it contains the theoretical fundaments that was used in order to develop this project. In chapter 2, it analyses the current situation of the voice and data infrastructure in Batan Center. It shows the communication among the others centers in Ecuador, it also will study and identify the requirements of designing and implementing an optimal multiservice network. In chapter 3, it sets a solution for the deficient current infrastructure in Batan Center, mainly the sizing of an infrastructure that allows the efficient network process, the structured cabling, the installation and configuration of the networking equipment and network services. In chapter 4, it describes an economical study about the project in order to determine if the project is economically viable and if it represents an optimal solution for the IESS medical center Finally in chapter 5, it exposes the conclusions about the project and final remarks that help to develop new others studies that are seemed like this.